PENGARUH LOCAL GOVERNMENT WEALTH, INTERGOVERNMENTAL REVENUE DAN OPINI AUDIT TERHADAP PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH PROVINSI DI INDONESIA SECARA ONLINE - Dewi Lesmanawati (Universitas Trunojoyo Madura, 2019)
The aim of this article is to examine the extent of the influence of local government wealth, intergovernmental revenue and audit opinion on disclosure of online financial statements of provincial governments in Indonesia.. The data of this research comprise 128 out of 32 provincial governments in Indonesia during 2014-2017, using purposive sampling method. The analysis techniques used were logistic regression. The results of this study show that the local government wealth and intergovernmental revenue has positive significant influence on disclosure of online financial statements, while audit opinion do not have significant influence on disclosure of online financial statements.